Analysis of power organization and political theory: The dynamics of complexity in the era of digital transformation - Asyha, Agus Faisal; Astuti, Yeni; Subandi, Subandi; Syarifudin, Encep; Makbuloh, Deden (Journal of Multidisciplinary Academic Business Studies, 2024)
Purpose: This study aims to analyze the interconnection between organizational theory, power, and politics in the context of digital transformation, focusing on identifying new patterns in organizational power dynamics and their implications for management effectiveness Research Methodology: This study adopts a qualitative meta-analysis of 150 academic articles from reputable journals (2000-2024) using Scopus, Web of Science, and JSTOR databases. The analysis used ATLAS.ti software for thematic coding and content analysis, with validation through expert panel reviews from 12 senior academics in the field of organizational theory. Results: This study identifies five transformative patterns in organizational power: the digitization of authority, hybridization of power structures, emergence of virtual politics, reconfiguration of the influence base, and evolution of control mechanisms. The developed analytical framework integrates digital, structural, and relational dimensions in the analysis of an organization’s power. Conclusions: Digital transformation reshapes processes and power, requiring managers to adapt their strategies to balance authority, relationships, and virtual influence arenas. Limitations: The major limitations include a focus on the formal organization of the technology and financial sectors and the dominance of literature from advanced economies. The research does not include a direct empirical analysis of power dynamics in purely virtual organizations. Contribution: This study contributes to the development of contemporary organizational theory through the integration of digital perspectives in power analysis and provides a practical framework for organizational political management in the digital era.